How to apply Simulation-Based Learning in Medical Education? - Said Said Elshamaa (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Simulation-Based Learning is considered the best alternative teaching and assessment tool that able to make the change in education, training, improving the quality and assessing the performance of the medical students. It helps students for acquiring many skills such as professionalism, communication, self-evaluation, time management, and teamwork. In addition, the use of simulation in medical education is based on many noble goals and ethical rules; it provides the best standards for patient care and safety, patient autonomy, and social justice. However, assessment of the application of simulation appropriateness depends on validity, reliability, and utility. Simulation has many types and classifications; it may be classified into human simulation such as role-play and standardized patient or non-human simulation such as manikin and the based computer simulation. It may be also classified according to the type or the fidelity. According to the type, it is classified into compiler-driven and event-driven, or according to the fidelity as a low, medium, and high-fidelity. There are specific criteria and steps that should be applied when designing a simulation course or operation a simulation training session as well as designing a skill checklist for ensuring a successful simulation application in medical education. However, many challenges and obstacles are still facing simulation implementation in medical education in different medical schools.